2012
DOI: 10.1007/s11033-012-2391-4
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal and post-natal screening of β-thalassemia and hemoglobin E genes in Thailand using denaturing high performance liquid chromatography

Abstract: We have developed methods based on PCR and denaturing high performance liquid chromatography (DHPLC) for rapid identifications of common β-thalassemia mutations found in Thailand. The β-globin gene was separately amplified by PCR on four different fragments covering eight most common β-thalassemia mutations including nucleotide -28 A-G, codon 17 (A-T), IVSI-1 (G-T), IVSI-5 (G-C), codon 26 (G-A or Hb E), codons 41/42 (-TTCT), codons 71/72 (+A) and IVSII-654 (C-T). After PCR amplification, heteroduplex was gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Although significance differences were also noted on Hb E and Hb F between the two conditions, the amount of Hb A 2 determined using the capillary electrophoresis system seems to be the most useful marker for initial differential diagnosis before being confirmed by DNA analysis. As for α‐thalassemia and β‐thalassemia , the DHPLC assays used in this study as shown in Fig. should prove useful in providing accurate genotyping platforms for these common high Hb F determinants in the region.…”
Section: Discussionmentioning
confidence: 99%
“…Although significance differences were also noted on Hb E and Hb F between the two conditions, the amount of Hb A 2 determined using the capillary electrophoresis system seems to be the most useful marker for initial differential diagnosis before being confirmed by DNA analysis. As for α‐thalassemia and β‐thalassemia , the DHPLC assays used in this study as shown in Fig. should prove useful in providing accurate genotyping platforms for these common high Hb F determinants in the region.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9]11 Patients in each ethnic population carry their own specific types of mutations, including a few very common ones and a variable number of rare ones. [7][8][9]11 Several molecular methods for the diagnosis of thalassaemia mutations have been described, including next-generation sequencing, 12 amplification refractory mutation system, 13,14 allele-specific oligonucleotide polymerase chain reaction, 15 denaturing high performance liquid chromatography (DHPLC), 16 reverse dot blot 17 and gap-polymerase chain reaction (Gap-PCR). 2,5,7 However, the main drawbacks of these methods are that they are expensive, labour intensive and have limited resolution.…”
Section: Introductionmentioning
confidence: 99%